2017
DOI: 10.11604/pamj.2017.28.93.11512
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome in adolescents in Lagos

Abstract: Introductionirritable bowel syndrome (IBS) is one of the functional gastrointestinal disorders (FGIDs) which has been well described in western populations especially as the commonest cause of recurrent abdominal pain The aim of this study was to document the prevalence of Irritable bowel syndrome (IBS) amongst children in western Nigeria and increase the aware ness of IBS amongst physicians who manage children with abdominal pain.MethodsThis was a cross-sectional study conducted amongst children aged 10-18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…However, two more recent epidemiological from Greece and Nigeria reported higher prevalence of IBS-M (47.9% and 53.6% respectively). In these two studies IBS-D and IBS-C were noted in 16.7%-19% and 27.4%-6.3% respectively[ 2 , 33 ]. In contrast, an Asian study noted an almost similar prevalence of IBS-C, IBS-D and IBS-M (29%-30%)[ 11 ].…”
Section: Epidemiology Of Ibsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, two more recent epidemiological from Greece and Nigeria reported higher prevalence of IBS-M (47.9% and 53.6% respectively). In these two studies IBS-D and IBS-C were noted in 16.7%-19% and 27.4%-6.3% respectively[ 2 , 33 ]. In contrast, an Asian study noted an almost similar prevalence of IBS-C, IBS-D and IBS-M (29%-30%)[ 11 ].…”
Section: Epidemiology Of Ibsmentioning
confidence: 98%
“…Several studies from Greece, Nigeria, South America and Sri Lanka have recognized IBS as the most prevalent FGID among children and adolescents (2.9%, 9.9%, 3.8%-6.4% and 3.6%-7% respectively)[ 6 - 9 , 33 - 36 ]. Many other studies have also reported a high prevalence of IBS in China (13.25%)[ 1 ], Nigeria (16%)[ 2 ] and Turkey (22.6%)[ 3 ]. In contrast to this, studies from United States have shown lower prevalence rates of IBS (2.8% and 5.1%)[ 37 , 38 ].…”
Section: Epidemiology Of Ibsmentioning
confidence: 99%
See 3 more Smart Citations